Optical properties of a single-colour centre in diamond with a green zero-phonon line - Smith, J; Grazioso, F; Patton, B; Dolan, P; Markham, M; Twitchen, D (IOP Publishing, 2011)
We report the photoluminescence characteristics of a colour centre in diamond grown by plasma-assisted chemical vapour deposition. The colour centre emits with a sharp zero-phonon line at 2.330 eV (λ = 532 nm) and a lifetime of 3.3 ns, thus offering potential for a high-speed singlephoton source with green emission. It displays a vibronic emission spectrum with a Huang-Rhys parameter of 2.48 at 77K. Hanbury-Brown and Twiss measurements reveal that the electronic level structure of the defect includes a metastable state that can be populated from the optically excited state. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.